Sistem Imbal Jasa Pada Agen BRILink: Sebuah Tinjauan Ekonomi Syariah - Setiawan, Adi; Putra, Adi (Jurnal Iqtisaduna, 2022)
ABSTRACT The purpose of this study was to determine the Service Fee System at BRILink Agents in Air Dikit District, Mukomuko Regency, from an Islamic Economic Perspective. This research is a field research using a qualitative descriptive method. Data collection techniques used are observation, interviews and documentation. The results of this study indicate that the BRILink Agent Service Fee System, Air Dikit District, Mukomuko Regency is a profit sharing system or service fee between BRI and BRILink agents with a fee percentage of 50%:50%. 50% for agents and 50% for BRI. The determination of the BRILink agent service rate, Air Dikit District, Mukomuko Regency, there is no provision for the nominal administrative fee from BRI charged to customers, it’s just that BRI provides standard rates with BRILink agents while the additional administrative fees in full are left to each BRILink agent, so BRILink agents can achieve the target of at least 200 transactions / month according to BRI provisions. Analysis of Islamic Economic Perspectives on BRILink Agent Service Fees, Air Dikit District, Mukomuko Regency, is in accordance with the principles of Islamic Economics, namely the principle of help, the principle of appropriateness/appropriateness, the principle/clear, and the principle of benefit. Keywords: Services, BRILink Agent, Islamic Economy